INTERPRETATION OF IBN QAYYIM AL-JAUZIYYAH ON SHIFA IN THE AT-TAFSIR AL-QAYYIM AND BADAA’IUT TAFSIR:Analysis of Johanna Pink's Typology - Roma Wijaya; Satria Tenun Syahputra (Wahana Islamika: Jurnal Studi Keislaman, 2023)
This article analyzes the interpretation of Ibn Qayyim Al-Jauziyyah with the typology theory of interpretation offered by Johanna Pink, a researcher at Freiburg University's interpretation. One of the terms being discussed here is shifa. The term shifa is still understood with theological arguments, so it escapes health sciences. Ibn Qayyim understood it as physical and psychological healing. This research is a library research type of qualitative research. The analysis used is Johanna Pink's typology: scholar’s commentaries, institutional commentaries, and popularizing commentaries. The primary source of this research is the book of Tafsir al-Bada'I at-Tafsir Ibn Qayyim and at-Tafsir al-Qayyim and other works by Ibn Qayyim. The secondary sources are books, articles, and magazines that have theme relevance. The results of this study are first, the verses interpreted by Ibn Qayyim al-Jauziyyah about shifa, the majority of which is that the Qur'an is an antidote to various psychological and physical ailments. Second, Tafsir Ibn Qayyim Al-Jauziyyah in the book al-Bada'I at-Tafsir Ibn Qayyim and at-Tafsir al-Qayyim seen from Johanna Pink's typological theory is included in the category of scientific interpretation, even though she did not directly write it down and but absorbed and collected by his student named Muhammad Uwais an-Nadwi. These results reveal the typological model of Ibn Qayyim's interpretation. Here the researcher recommends conducting research on Ibn Qayyim with hermeneutical analysis, to find the background of Ibn Qayyim's interpretation in depth.